Normal human lymph node T follicular helper cells and germinal center B cells accessed via fine needle aspirations - Havenar-Daughton, Colin; Newton, Isabel G.; Zare, Somaye Y.; Reiss, Samantha M.; Schwan, Brittany; Suh, Min Ji; Hasteh, Farnaz; Levi, Gina; Crotty, Shane (Journal of immunological methods, 2020)
Germinal centers (GC) are critically important for maturation of the antibody response and generation of memory B cells, processes that form the basis for long-term protection from pathogens. GCs only occur in lymphoid tissue, such as lymph nodes, and are not present in blood. Therefore, GC B cells and GC T follicular helper (TFH) cells are not well-studied in humans under normal healthy conditions, due to the limited availability of healthy lymph node samples. We used a minimally invasive, routine clinical procedure, lymph node fine needle aspirations (LN FNAs), to obtain LN cells from healthy human subjects. This study of 73 LNs demonstrates that human LN FNAs are a safe and feasible technique for immunological research, and suggests benchmarks for human GC biology under noninflammatory conditions. The findings indicate that assessment of the GC response via LN FNAs will have application to the study of human vaccination, allergy, and autoimmune disease.